Pembangunan Karakter Disiplin Taruna Pada Politeknik Pelayaran Barombong - Gassing; Mukhtar, Umar; Haryani, Rina; Lolo Tandung, Albertha; Sukur; Saleh, Muhammad; Wisudawanto, Feri (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Character development focuses on building soft skills competency, in this case, the care activities in the implementation of the education and training process are able to create a fresh environment and foster enthusiasm or enthusiasm for learning and training in cadets to realize human resources in transportation that are physically fit, professional in how they work and have ethic. The purpose of this research is to find out how the implementation of the disciplinary character development of cadets, the method used is qualitative research with a phenomenological approach with a type of case study research with Politeknik Pelayaran Barombong Cadets 61 unit. The data were obtained from observations of the daily activities of cadets and interviews to Head of the Center for Character Development, Caregivers, Company Officers, Counselors and cadets. The data were analyzed using data reduction measures, display data and verification, based on the results of the study it can be concluded that the character development of the discipline level towards discipline within the campus is classified as high, it can be seen from the daily activities that are realized in all activities at the Character Development Center. From the research, it is hoped that discipline can be impproved by formulating policies and activity programs and provide input in increasing attention in instilling disciplinary values ​​that include intracurricular, co-curricular and extracurricular activities.